Tradisi Khitanan Anak Perempuan Dalam Tinjauan Sosiologi Agama: The Tradition of Female Circumcision in Sociology of Religion Review - Wahyuni; Abd Halim K (IAIN Parepare, 2023)
This study focuses on the female circumcision tradition in a sociological review of religion. The purpose of this study was to determine the procession and meaning contained in the female circumcision tradition in the Bittoeng sub-district, Duampanua Pinrang sub-district. This research is a type of qualitative research. The subjects in this study were the people of Bittoeng Village, Duampanua District, Pinrang Regency. Data collection techniques were carried out through observation, interviews and documentation. Equipped with data analysis techniques using data reduction, and data presentation. The results show that the implementation of the circumcision tradition for girls aged 4-7 years, is carried out in the morning, which is circumcised by a traditional birth attendant by using certain materials that have the same symbols and meanings. believed by the people of Bittoeng village. The meaning contained is carried out on the basis of culture and religion, and social and parental expectations of children who have been circumcised to Allah SWT. in achieving a good in the future. The Tradition of Girls' Circumcision in Sociology of Religion, all communities in the Bittoeng village, both natives and transferees, are obliged and must carry out the tradition of female circumcision in addition to being believed to be a religious order and local tradition as well as forming a shared identity and acceptance of religious communities in their environment.